Implementing Inclusive Education: Experiences of School Leaders in Change Management - Bilbokaitė, Renata; Bilbokaitė-Skiauterienė, Ieva; Valuntinaitė, Violeta (Special Education, 2024)
Education for all is one of the goals of sustainable development, but in order to ensure it globally, it is necessary to implement political goals at different levels and constructively and proactively manage changes in educational institutions. The implementation of inclusive education is a long-term process of educational transformation, the management of which is largely the responsibility of educational leaders. The purpose of the study is to analyze the experiences of school leaders in managing changes in inclusive education. Research methodology. The conducted research is based on the methodological approach of qualitative research, with the aim of obtaining the best possible understanding of the phenomena of reality through the research (Flick, 2018). The method of semi-structured interview was used for data collection. The research instrument was constructed on the basis of the analysis of scientific literature (Keles, 2024, Phillips, Klein, 2023, Struyf et al., 2022, Kauffman, 2020, Bortini et al., 2016, Hayes, 2014, etc.). The research was conducted in April-May 2024. The content analysis method was used for the analysis of research data. The study involved 35 heads of Lithuanian general education schools that provide primary, basic, and secondary education – principals, deputies, and heads of departments. The research ethics and data protection principles were followed during the research. The results of the study revealed that leaders of educational organizations associate the concept of inclusive education with the recognition of the individual needs and abilities of each student, the principles of equality and equal opportunities, and educational assistance. The positive attitudes of the heads of the institution towards inclusive education at the ideological, conceptual and value levels are noticeable, but the principles of inclusion are more actualized in the context of more severe disabilities and special needs. School leaders have a variety of experiences in building an inclusive school and managing change. In the process of creating a strategic inclusive culture, teachers experience unfavorable attitudes, various difficulties in organizing the basic educational process and ensuring educational assistance, monitoring limitations. Change management also becomes more complicated in additional managerial processes: there is a lack of cooperation and partnership between communities; insufficient competence of existing pedagogues and lack of educational staff; changes in inclusive governance are also held back by limited finances and poor infrastructure. The positive experiences of school leaders have been experienced by successfully mobilizing the school community’s cooperation, teamwork, and networking (creating a common network with schools, parents’ community, and other partners). In successful cases, when creating the culture of an inclusive school, managers also mention the effectiveness of educational support, the usefulness of teamwork, and the application of various methods closer to personalized child education in the educational process. School leaders name three main competences, the development of which they would like to pay more attention to in the context of creating an inclusive school: leadership of people, strategic and educational institution management, and partnership and cooperation competences. Heads of educational institutions during inclusive education change management improve the aforementioned competences in the form of professional learning and development – purposeful participation in events and short-term mobility projects, the content and activities of which can help expand partnership and cooperation, improve strategic and change management.